Republic of Congo : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Congo. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper discusses key findings of the Second Review Under the Poverty Reduction and Growth Facility (PRGF) for the Republic of Congo. Policy implementation through the first half of 2009 was satisfactory. All quantitative performance criteria and all but one of the structural benchmarks were met. The non-oil basic primary deficit target for end-June was observed by a comfortable margin. Progress toward observing the Heavily Indebted Poor Countries (HIPC) floating completion point triggers has accelerated recently, and the authorities are making a strong effort to reach the completion point by year-end.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet